Analysis of economy, thermal efficiency and environmental impact of geothermal heating system based on life cycle assessments. (1st December 2021) - Xia, Z.H.; Jia, G.S.; Ma, Z.D.; Wang, J.W.; Zhang, Y.P.; Jin, L.W.
Highlights: A comprehensive evaluation for geothermal heating systems was proposed. Butted well performs better considering economy, thermal efficiency and environmental impact. Geothermal heating systems are more environmentally friendly than conventional heating. Life cycle saving of geothermal systems is more sensitive to income and discount rate. Abstract: The deep buried coaxial and horizontally-butted borehole heat exchangers are the two typical wells for geothermal utilization in space heating. The economic indexes, heat extraction performance and environmental impact of the two wells are crucial for actual projects. In this study, the Monte Carlo simulation and sensitivity analysis based on life cycle saving are employed to evaluate the economy of the two borehole heat exchanger systems. The heat extraction considering both performance and economic factors is examined by the levelized cost, while the environmental impact is assessed by the carbon intensity analysis. The results showed that the payback periods of a coaxial borehole heat exchanger system and a horizontally-butted borehole heat exchanger system are 6.7–9.2 years and 9.1–11.7 years respectively, and the life cycle saving of a butted borehole heat exchanger may reach a high value after 25 years of operation. The sensitivity of life cycle saving for both coaxial and horizontally-butted borehole heat exchangers is mainly governed by heating income, discount rate, and non-depreciable initial investment. The heat production capacity of the butted borehole heat exchanger system is 1128–1342 kW, which is twice as much as that of coaxial borehole heat exchanger. From the life cycle perspective, the levelized cost of energy and carbon intensity of the coaxial borehole heat exchanger is $ 8.67–9.35/GJ and 70.43–80.86 g(CO2 )/kWh, slightly higher than those of the butted borehole heat exchanger. It can be proved that the two borehole heat exchangers are more in line with the low-carbon policy than the traditional heating methods, and the well construction and operation phase contributes a major carbon emission from the perspective of the life cycle.